Improving Language Skills Through Picture Puzzle Method (PTK at PAUD Mandiri Sejahtera 2 Seluma Regency) - Revaini, Antin; Jusmadi, Evriyeni; Asnawati, Asnawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the improvement of children's language skills with the picture puzzle method at PAUD Mandiri Sejahtera 2, Seluma Regency. This type of research is Classroom Action Research (CAR) or also called Classroom action research with the procedure used in the form of a cycle. The subjects of this study were children in group B at PAUD Mandiri Sejahtera totaling 10 children. The study was conducted in two cycles and two meetings. Data analysis was carried out in qualitative and quantitative descriptions with the emphasis being used to determine the improvement of the process expressed in a predicate, while quantitative analysis was used to determine the improvement of results using percentages. Based on the results of the study, the improvement of children's language skills with the picture puzzle method at PAUD Mandiri Sejahtera 2 in cycle I meeting I with a percentage of 39.37%, in cycle I meeting II with a percentage of 46.25%, cycle II meeting I with a percentage of 58.12% and cycle II meeting II with a percentage of 83.12%. The conclusion of the research results is that using the picture puzzle method in learning can improve language skills in children at PAUD Mandiri Sejahtera, Seluma Regency, as evidenced by the increase in cycle II, meeting II, with a percentage achievement of 83.12% with the criteria of developing very well (BSB).